Impact of restriction of over-the-counter sales of antimicrobials on antimicrobial resistance in Escherichia coli from community-onset urinary tract infections in inner São Paulo State, Brazil - Rodrigues, Fernanda Saad [UNESP]; Amat, Helena Ribeiro Aiello [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP] (Public Library of Science (PLoS), 2021)
Background Antimicrobial resistance in community-associated infections is an increasing worldwide concern. In low-to-middle income countries, over-the-counter (OTC) sales of antimicrobials without medical prescription have been blamed for increasing consumption and resistance. We studied the impact of restriction of OTC sales of antimicrobials in Brazil (instituted in October 2010) on resistance trends of Escherichia coli from community-onset urinary tract infections. Methods We analyzed monthly resistance trend of Escherichia coli from community-onset urinary tract infections from 2005 through 2018. The data were submitted to interrupted time series analysis in both linear and Poisson regression models. Results We found impact on cefazolin (p<0.001) and amikacin (p<0.001) resistance as immediate impact of the intervention, and no beneficial impact on resistance to ciprofloxacin, ceftriaxone or sulfamethoxazole-trimethoprim. Conclusion At the present study, we found that OTC sales restriction did not generally impact on antimicrobial resistance.